Meningkatkan Aktivitas Belajar Siswa Kelas V Menggunakan Alat Peraga IPA Sistem Pernapasan Manusia di SD Islam Nurul Huda Jatipulo Jakarta - Neisya Pratiwi; Harlinda Syofyan (Journal on Education, 2023)
This research is motivated by learning activities, enthusiasm, and interest in learning owned by fifth-grade students at SD Islam Nurul Huda Jatipulo has decreased, especially in science subjects due to reduced student interest in learning, and less interesting ways of learning so that students are easily bored learning. The purpose of this class action research is to increase the learning activities of fifth-grade students with the use of science props Human respiratory system. The subjects of this class action research are fifth-grade students of SD Islam Nurul Huda Jatipulo Jakarta 2022/2023. The research subjects totaled 15 students consisting of 7 male students and 8 female students. The type of research used is classroom action research (PTK) which includes several cycles consisting of stages such as planning, action, observation, and reflection. The data analysis techniques used were descriptive qualitative and descriptive quantitative. The results of this study are that in cycle I the percentage of the number of students who met the good category was only 20%, then increased to 80% in cycle II. The average percentage of student learning activities in each aspect continued to increase in cycle I with an average percentage of 43% which then increased in cycle II with an average percentage of 87%.